Analisis Sistem Penyaluran Kredit Perbankan (Studi Kasus Pada PT BPR Supra Artapersada Kantor Pusat Operasional) - Zhafirah, Luthfiah; Sudarma, Ade; Suherman, Acep (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The banking industry has a role to support the economy which can be done through collecting funds and channeling it back in the form of credit, so that the bank is tasked with being a financial intermediary that connects existing funds from economic units with excess funds to economic units that need financial assistance (deficit), whether it's for working capital, investment and consumption (Effendi 2020). This study aims to find out whether the credit distribution system implemented by PT BPR Supra Artapersada at the Operational Head Office is based on procedures. Use of Qualitative Description as a method in this study, the data used is by collecting data from research objects and analyzing procedures and credit distribution systems. The research data was collected through interviews, observation, and documentation. The results of the research show that credit distribution processes are carried out in various stages of the procedure, namely: the credit application stage, the interview stage, data analysis, debtor visits, collateral assessment, credit analysis, credit decisions, credit binding, and credit disbursement. By having an in-depth understanding of this process and the factors that influence it, we can identify areas for improvement and implement relevant measures to enhance the success of the credit distribution system.